How Institutional Investors’ Alternative Funding and Investment Opportunity Impact Education System? The Case of Saudi Arabia - Nasser ALSHAREEF (Communications of International Proceedings, 2023)
The investment made in the educational system is an indicator of a nation's capacity for global expansion and innovation. A successful model of institutional investment's involvement in the growth of clean energy infrastructure, entrepreneurship, the eradication of poverty, and the promotion of corporate social responsibility and corporate development has been established. There is a dearth of study in the literature addressing institutional investors and the funding of the educational system. This study gives the Saudi educational system with another long-term financing stream while also giving investors a way to choose their investments with minimum interference from the government. According to the research, the university will increase its funding possibilities through institutional investors through government efforts. This will relieve pressure on the government and open up a sizable market for institutional investors. The Saudi educational system will be improved and the "Saudi Vision 2030" will be directly impacted by this institutional investor and sustainable financing mechanism for university research.
Keywords: The Saudi Arabian Monetary Authority; Institutional Investors; Alternate Funding Opportunity; Saudi Arabia Education; Vision 2030; Saudi Global Knowledge Index (GKI)